2021
DOI: 10.3390/ijerph18105059
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Popliteal Nerve Block with Short-Acting Lidocaine in the Surgical Treatment of Ingrown Toenails

Abstract: Background: Digital nerve block (DB) is a commonly utilized anesthetic procedure in ingrown toenail surgery. However, severe procedure-related pain has been reported. Although the popliteal sciatic nerve block (PB) is widely accepted in foot and ankle surgery, its use in ingrown toenail surgery has not been reported. Therefore, this study aimed to investigate the safety and effectiveness of PB in the surgical treatment of ingrown toenails. Methods: One-hundred-ten patients surgically treated for an ingrown toe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…26 Also, Kim et al reported that PPB demonstrated less pain, extended sensory block duration, and fewer repeated injections compared to DB. 28 Our results showed that both groups had comparable PONV, hypotension, and bradycardia. PONV occurred in 8 (26.67%) patients in PPB group and 3 (10%) in FIB group.…”
Section: Discussionsupporting
confidence: 52%
“…26 Also, Kim et al reported that PPB demonstrated less pain, extended sensory block duration, and fewer repeated injections compared to DB. 28 Our results showed that both groups had comparable PONV, hypotension, and bradycardia. PONV occurred in 8 (26.67%) patients in PPB group and 3 (10%) in FIB group.…”
Section: Discussionsupporting
confidence: 52%
“…Elsewhere, the anesthetic techniques were well defined. Kim and colleagues [13] talked about the use of short-acting lidocaine in ultrasound-guided popliteal nerve block for ingrown toenail surgical therapy. Nevertheless, digital blocks containing non-epinephrine local anesthetic drugs are also Prospective study Patients (25%) who had conservative treatment and avulsion of the nail had recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The surgeries are amenable to various anesthetic techniques. Kim and colleagues [13]. discussed using ultrasoundguided popliteal nerve block using short-acting lidocaine in the surgical treatment of ingrown toenails.…”
Section: Introductionmentioning
confidence: 99%